2021
DOI: 10.1186/s12962-021-00332-1
|View full text |Cite
|
Sign up to set email alerts
|

Level and determinants of county health system technical efficiency in Kenya: two stage data envelopment analysis

Abstract: Background Improving health system efficiency is a key strategy to increase health system performance and accelerate progress towards Universal Health Coverage. In 2013, Kenya transitioned into a devolved system of government granting county governments autonomy over budgets and priorities. We assessed the level and determinants of technical efficiency of the 47 county health systems in Kenya. Methods We carried out a two-stage data envelopment ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Further, stakeholders in the Kenyan health system identified human resources for health (HRH) as a potential determinant of health system efficiency at the county level [13]. The second phase of the study measured the technical efficiency of the 47 county health systems in Kenya [14]. The study reported a mean technical efficiency of county health systems of 70%, and found that a higher HIV prevalence was associated with lower technical efficiency of county health systems, while higher population density, county absorption of development budgets, and quality of care provided by healthcare facilities were associated with higher county health system efficiency [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, stakeholders in the Kenyan health system identified human resources for health (HRH) as a potential determinant of health system efficiency at the county level [13]. The second phase of the study measured the technical efficiency of the 47 county health systems in Kenya [14]. The study reported a mean technical efficiency of county health systems of 70%, and found that a higher HIV prevalence was associated with lower technical efficiency of county health systems, while higher population density, county absorption of development budgets, and quality of care provided by healthcare facilities were associated with higher county health system efficiency [14].…”
Section: Introductionmentioning
confidence: 99%
“…The second phase of the study measured the technical efficiency of the 47 county health systems in Kenya [14]. The study reported a mean technical efficiency of county health systems of 70%, and found that a higher HIV prevalence was associated with lower technical efficiency of county health systems, while higher population density, county absorption of development budgets, and quality of care provided by healthcare facilities were associated with higher county health system efficiency [14]. This phase informed the selection of case study counties for the subsequent phase.…”
Section: Introductionmentioning
confidence: 99%
“…We purposively selected four counties using the level of health system technical efficiency reported in phase two of the broader study 17 as a key selection criterion (Table 1). We then took into consideration other county characteristics that were identified by the quantitative efficiency analysis as determinants of efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…In the first phase of the study, a systematic literature review 13 and stakeholder engagement 14 were conducted that reported PFM processes as key determinants of health system efficiency globally and at the county level in Kenya, respectively. In the second phase, a quantitative assessment of county level health system efficiency and its determinants identified PFM as one of the key determinants of county level efficiency in Kenya 15 . In this third phase of the study, we explore in-depth how the factors identified in previous study phases interact with county health system efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…We selected four cases - counties - using the level of technical efficiency reported in phase two of the Kenya Efficiency Study (Barasa et al ., 2021). We then took into consideration other county characteristics that were identified by the quantitative efficiency analysis as determinants of efficiency.…”
Section: Methodsmentioning
confidence: 99%